me ajudem por favor :]
Anexos:
![](https://pt-static.z-dn.net/files/d93/9fb9f5df1a85636f927cb0f281d7fdf3.jpg)
Soluções para a tarefa
Respondido por
1
Resposta:
1
Explicação passo a passo:
f(-2) = -4(-2)+2
f(-2) = 8+2
f(-2) = 10
f(3) = -4(3)+3
f(3) = -12+3
f(3) = -9
f(-2) + f(3) = 10 - 9 = 1
Perguntas interessantes
Português,
7 meses atrás
Matemática,
7 meses atrás
Filosofia,
7 meses atrás
Português,
7 meses atrás
Matemática,
7 meses atrás
Inglês,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás